2018
DOI: 10.1073/pnas.1800442115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental changes on vegetable and legume yields and nutritional quality

Abstract: Environmental changes threaten agricultural production, food security, and health. Previous reviews suggest that environmental changes will substantially affect future yields of starchy dietary staples. To date, no comprehensive global analysis of the impacts of environmental change on (nonstaple) vegetables and legumes-important constituents of healthy diets-has been reported. We systematically searched for articles published between 1975 and 2016 on the effects of ambient temperature, tropospheric carbon dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(101 citation statements)
references
References 24 publications
4
89
0
8
Order By: Relevance
“…Reduced availability of other nutritionally relevant crops such as fruits, vegetables, nuts and legumes would also threaten food security, especially from a dietary (or nutrient) diversity perspective. A recent systematic review on the effect of environmental changes on vegetable and legume yields and nutritional quality found that under a business-as-usual scenario, environmental changes are likely to have substantial negative impact on yields [10], in keeping with our findings presented here regarding fruit, nuts and seeds.…”
Section: Comparison With Other Literaturesupporting
confidence: 90%
See 2 more Smart Citations
“…Reduced availability of other nutritionally relevant crops such as fruits, vegetables, nuts and legumes would also threaten food security, especially from a dietary (or nutrient) diversity perspective. A recent systematic review on the effect of environmental changes on vegetable and legume yields and nutritional quality found that under a business-as-usual scenario, environmental changes are likely to have substantial negative impact on yields [10], in keeping with our findings presented here regarding fruit, nuts and seeds.…”
Section: Comparison With Other Literaturesupporting
confidence: 90%
“…A search of seven databases was carried out in conjunction with a second systematic review evaluating the impact of environmental change on vegetables and legumes [10]. Databases searched were OvidSP MED-LINE, OvidSP EMBASE, EBSCO GreenFILE, Web of Science Core Collection and OvidSP AGRIS: to identify papers on fruits two additional databases were searched: Scopus and OvidSP CAB Abstracts.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced consumption of livestock-based products (e.g., meat, eggs, and milk) and reduced food waste have also been demonstrated as effective strategies for alleviating future agricultural land and water requirements, especially in conjunction with liberalized trade [79,92,94]. There are also the impacts of higher CO 2 concentrations on the quality of the nutrients in food [106], indicating a need to link food impacts and mitigation strategies at the global-scale.…”
Section: Agro-economic Modelsmentioning
confidence: 99%
“…These crops also fix nitrogen because of their symbiosis with Rhizobium bacteria, which makes them attractive crops for soil improvement in farming systems 2 . However, increased abiotic stress such as heat, drought and salinity, and high pressure of disease and insect pests under climate change will decrease yield and quality of existing legume varieties 3 .…”
Section: Introductionmentioning
confidence: 99%